(untitled) (Symposium on Life and Environmental Sciences, 2026)
This article examines the role of international experience in strengthening local budget revenues and identifies practical directions for its application in national conditions. The study analyzes global best practices in property taxation, intergovernmental fiscal transfers, digital tax administration, and public–private partnerships (PPP). Based on comparative data, the paper demonstrates that in many developed economies local taxes account for 60–75% of local government revenues, while property tax alone contributes 25–45%. In contrast, in many transition economies this indicator remains below 20%, indicating significant untapped fiscal potential. The paper proposes a phased reform roadmap for improving revenue mobilization at the local level, enhancing fiscal autonomy, and ensuring equitable regional development. The findings may serve policymakers, local authorities, and public finance specialists in designing evidence-based reforms.